Diffusion bonding of titanium and AA 7075 aluminum alloy dissimilar joints—process modeling and optimization using desirability approach. Issue 1 (September 2016) - Rajakumar, S.; Balasubramanian, V.
Abstract The major difficulty when joining commercially pure titanium (cp-Ti) and aluminum (Al) lies in the existence of formation of oxide films and brittle intermetallics in the bond region. The diffusion bonding (DB) process parameters such as bonding temperature, bonding pressure, and holding time play a major role to determine the joint strength. In this investigation, an attempt was made to develop an empirical relationship to predict the lap shear strength, interface layer thickness, and weld interface hardness of diffusion-bonded cp-Ti–AA 7075 aerospace aluminum alloy, incorporating above said parameters. Response surface methodology (RSM) was applied to optimize the DB process parameters to attain the maximum shear strength, hardness, and optimum interface layer thickness of the joint. Lap shear tensile test was performed to evaluate shear strength of joints. From this investigation, it is found that the bonds fabricated with the bonding temperature of 510 °C, bonding pressure of 17 MPa, and holding time of 37 min yielded maximum shear strength of 87 MPa, hardness of 163 HV, and interface layer thickness of 7 μm, respectively.